Social norm, the informal sector and unemployment - Ann-Sofie Kolm; Birthe Larsen (Copenhagen Business School (CBS), Department of Economics, 2002)
While examining the macroeconomic effects of increased government control of the informal sector, this paper develops a two-sector general equilibrium model featuring matching frictions on the labour market and a social norm. Conducting informal work, or employing a worker infor- mally, is associated with expected punishment fees and payments of a moral cost, given that there is a social norm against tax evasion. This framework facilitates an analysis of how wage setting, unemployment and the size of the informal sector are affected by punishment policies, which has been ignored in the previous literature. Furthermore, the inclusion of an endogenously determined norm against tax evasion may explain differences in-between regions or countries in relative sizes of the formal and the informal sectors for similar tax- and punishment policies.
hdl:10398/7586
Keywords: H26; J64; 330; Tax evasion; informal sector; matching; bargaining; unemployment